Multifunctional Lateral Transition‐Metal Disulfides Heterojunctions. (18th June 2020) - An, Yipeng; Hou, Yusheng; Wang, Kun; Gong, Shijing; Ma, Chunlan; Zhao, Chuanxi; Wang, Tianxing; Jiao, Zhaoyong; Wang, Heyan; Wu, Ruqian
Abstract: The intrinsic spin‐dependent transport properties of two types of lateral VS2 |MoS2 heterojunctions are systematically investigated using first‐principles calculations, and their various nanodevices with novel properties are designed. The lateral VS2 |MoS2 heterojunction diodes show a perfect rectifying effect and are promising for the applications of Schottky diodes. A large spin‐polarization ratio is observed for the A‐type device and pure spin‐mediated current is then realized. The gate voltage significantly tunes the current and rectification ratio of their field‐effect transistors. In addition, they all demonstrate a sensitive photoresponse to blue light, and could be used as photodetector and photovoltaic device. Moreover, they generate an effective thermally driven current when a temperature gratitude appears between the two terminals, suggesting them as potential thermoelectric materials. Hence, the lateral VS2 |MoS2 heterojunctions show a multifunctional nature and have various potential applications in spintronics, optoelectronics, and spin caloritronics. Abstract : The intrinsic spin‐resolved transport properties of two types of lateral transition‐metal disulfides VS2 |MoS2 heterojunctions are unveiled, and their various multifunctional nanodevices are designed. The lateral VS2 |MoS2 heterojunctions are promising for the applications of rectifying diodes with a perfect rectification ratio, spin filters with large spin‐polarization ratio, field‐effect transistors, photodetectors, photovoltaic devices, and thermoelectric materials.